PENGARUH RASIO KEUANGAN DALAM MEMPREDIKSI PERTUMBUHAN LABA - Dwi Suryani; Mujino Mujino; Risal Rinofah (Jurnal Ilmiah Manajemen dan Bisnis, 2020)
This study aims to determine the effect of financial ratios consisting of current ratio, debt to equity ratio, total asset turnover, and net profit margin in predicting profit growth. This study took samples of the basic and chemical industry companies listed on the Indonesia Stock Exchange from 2013 to 2018. The sampling technique uses purposive sampling technique with samples used by 10 companies over a period of 6 years so that there are 60 samples in total. The results showed that the simultaneous current ratio, debt to equity ratio, total asset turnover, and net profit margin had a significant effect in predicting profit growth. Partially the debt to equity ratio and net profit margin have a significant positive effect in predicting profit growth. However, the current ratio does not have a significant negative effect in predicting earnings growth, while total asset turnover does not have a significant positive effect in predicting earnings growth.